Determination of essential mineral and heavy metals in selected ready to eat canned seafood products commercially available in east coast of peninsular Malaysia. - Ismail, Nurasyikin (Universiti Sains Malaysia, 2016)
The objective of this study was to determine the composition of essential mineral and heavy metals in selected ready to eat (RTE) canned seafood products commercially available in East Coast of Peninsular Malaysia. The compositions of essential mineral in the products were compared with recommended intake for population in Malaysia and the levels of heavy metal in selected canned food were also determined,.. Ten samples of selected canned seafood product were purchased form 5 supermarket around Kota Bharu, Kelantan. Microwave digestion was used for sample digestion and extraction and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to determine macro mineral (Na, Mg, K, Ca), trace mineral (Mn, Fe, Cu, Zn, Se) and heavy metal (Al, As, Cd, Sb, Pb) in selected canned seafood products. The range concentration of macro mineral: Na, Mg, K, Ca in selected canned foods were found within 0.575 - 3.510 mg/kg, 0.057 - 0.116 mg/kg, 0.357 - 1.002 mg/kg and 0.033 - 0.0787 mg/kg respectively. These concentrations of essential metals are in the range of human necessities. For trace mineral, the concentration of Cr, Mn, Fe, Cu, Zn and Se were ranged within 0.014 - 0.029 mg/kg , 0.008 - 0.308 mg/kg, 0.003 - 0.041 mg/kg, 0.022 - 0.261 mg/kg, 0.107 - 0.450 mg/kg and 0.011 - 0.043 mg/kg. While the concentration of heavy metal: Al, As, Cd, Sb and Pb were within the range of 0,116 - 4,707 mg/kg, 0,014 - 0,029 m/kg, 0.012 - 0.061 mg/kg, 0.001 - 0.094 mg/kg , < 0.001 mg/kg and 0.003 - 0.009 mg/kg respectively. In a conclusion, the concentrations of heavy metals being very negligible in most of the samples and was below the permissible limit according to Food Act 1983 and food regulation 1985. This indicate that these foodstuffs are reasonably safe from metal toxicity. However a few samples had slightly higher concentrations of these metals, although the concentration are still below the permissible limit, this kind of metals can be very harmful to human being even at low concentration. Thus regular examination of these items should be demanded before products distributed to the market.